PENGARUH MOTIVASI, DISIPLIN DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS PEGAWAI PADA KANTOR CAMAT TENGGARONG KOTA KABUPATEN KUTAI KERTANEGARA - Eriyanto, Hendro (EKONOMIA, 2013)
This study aimed to determine the effect of motivation , discipline and leadership on the productivity of employees at Head Office Tenggarong Kertanegara Kutai regency . In addition , this study also to know that the most dominant factor in increasing productivity of employees at Head Office Tenggarong Kertanegara Kutai regency .           Based on the analysis of the hypothesis that the first hypothesis suggested that motivation , discipline and leadership together significantly positive effect on the productivity of employees at Head Office Tenggarong Kertanegara Kutai regency and the second hypothesis suggested that the most dominant motivational factors affect employee productivity at the Head Office of the Kutai regency Kertanegara Tenggarong acceptable because together the variables of motivation , discipline and leadership have influence on the productivity of employees working at Head Office Tenggarong Kertanegara Kutai regency . Influence of these variables Analyses of test F , F count is equal to the value of 25.004 with a significance level of 0.000 ( 95% confidence level ) and the F table at 8.58 , which means for 25.004 F count > F table 8.58 , then the hypothesis acceptable because according to the criteria of F count > F table . So, when seen from the significant value of 0.000 is less than α level of 5 % . It can be concluded that the variables motivation , discipline and leadership variables variables significantly affect employee productivity on the Tenggarong City District Office Kutai Kertanegara .          The contribution of the variables X1 , X2 and X3 on Y , ie R = 0.791 ( 79.1 % ) and R Square of 0.625 ( 62.5 % ) . It means that there are other factors beyond the study that also affect the productivity of employees at Head Office Tenggarong Kertanegara Kutai regency .          T count results for each variable are as follows : motivation variable of 4.730 with a significance value of 0.000 is smaller than 0.05 and t table is 1.678 , which means t count of 4,730 > 1,678 t table , then the hypothesis is accepted because according to criteria t count > t table so evident that motivation significantly influence employee productivity . Variable discipline of 2.056 with a significance value of 0.046 is smaller than 0.05 and t table of 1,678 , which means t count of 2,056 > 1,678 t table , so that proved that disciplinary significant effect on employee productivity . and leadership variable t value of 1.066 with a significance value of 0.292 is greater than 0.05 . Which means that t < t table , so it is not proven that the leadership of a significant effect on employee productivity .